First syntaxonomical contribution to the invasive Ailanthus altissima (Mill.) Swingle forest communities at its southern limit in Europe - Silvia Montecchiari; Marina Allegrezza; Veronica Pelliccia; Giulio Tesei (Plant Sociology, 2020)
Ailanthus altissima (tree of heaven), an invasive alien tree native to China, has become invasive all over the world and in Italy is present in all the administrative regions where it can form dense forest communities. Although there are several ecological studies on this species there is a lack of floristic-vegetational data for southern-Europe. The study presents the results of a floristic vegetational study on A. altissima forest communities of central Italy that aims to highlight the possible floristic-vegetational autonomy of these coenoses. The results have allowed the characterization of A. altissima coenoses at the ecological, biogeographic, syntaxonomic and landscape levels. These represent first A. altissima syntaxa described for the Italian peninsula and for southern-Europe. We propose two new sub-Mediterranean and Mediterranean associations comprised in the recently described alliance Lauro nobilis-Robinion pseudoaciae, in the Chelidonio-Robinietalia order and the Robinietea class: Asparago acutifolii-Ailanthetum altissimae: forest community with stratified structure and high canopy density on the warmer slopes of the hills in dry soil conditions and low anthropic disturbance and Aro italici-Ailanthetum altissimae: paucispecific forest communities with a monolayered structure typically found in agricultural, and peri-urban areas on pelitic, alluvial silty-sandy substrates, in conditions of edaphic humidity and high anthropogenic disturbance. The comparison with literature data highlights the autonomy of these associations of the sub-Mediterranean and Mediterranean alliance Lauro nobilis-Robinion pseudoacaciae alliance from the Balloto nigrae-Ailanthetum altissimae association of the Central and SE-European Balloto nigrae-Robinion pseudoacaciae alliance.